Bimbingan Kelompok Berbasis Islam untuk Meningkatkan Penyesuaian Diri Santri Pondok Pesantren Al Ishlah Darussalam Semarang - Maghfur, Syaban (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
There is a tendency to decrease attitudes for early-stage santri in terms of self-adjustment which is influenced, among others, by the interest of some santri, many of them are because of the direction of parents. If such symptoms are not immediately addressed then adjustment becomes a serious problem among the early-stage santri. That need to be given the type of guidance that can help the difficulties of the students in the adjustment in boarding school. One of the efforts that can be done is the provision of Islamic-based group guidance services. The main problem is whether the guidance of Islamic-based groups can improve the early adjustment of student students at Al Ishlah Darussalam Islamic Boarding School Semarang? The purpose of this study is to find out the guidance of Islamic-based groups can improve the adjustment of early students in Al Ishlah Darussalam Islamic Boarding School Semarang. The Pre-Test and Post-Test Design Group. The population of this study is the initial level of students in Al Ishlah Darussalam Islamic Boarding School Semarang academic year 2016/2017 which amounted to 32 santri. The results of this study indicate that the guidance of Islamic-based groups can improve the adjustment of early santri level students in Al Ishlah Darussalam Islamic Boarding School Semarang based on the comparison of z count 4.994> z table 1.96 with probability = 0, 000 <0.05. The rate of adjustment before the guidance of the Islamic-based group was 62.04% and the level of adjustment after the guidance of the Islamic based group by 70.57%. In this case, there was an increase of 8.53%. Based on these results, the researcher gives suggestion to the custodian of pesantren to facilitate guidance and counseling to help santri adjustment to make it easier, involving the alumni of pesantren who are competent in the field of guidance and counseling.